POLARIMETRIC INVESTIGATION OF BL LAC. - Hagen-Thorn, V. A.; Yakovleva, V. A. (Одеські астрономічні публікації, 2017)
The extensive homogeneous set of polarimetric observations of BL Lac (1969-1991) has been obtained at Astronomical Observatory of St.-Petersburg University. We discuss the general polarization behavior of the object. The existence of the preferable direction of polarization (in the range between 20 and 30 degrees) as well as the dependencies between polarization parameters and between the polarization and brightness is found. In the individual sources responsible for variability the degree of polarization is as high as 50synchrotron nature of these sources is undoubted.